Cinema, novel, intertextuality and hermeneutics: The imaginaries of modernization in Mexico City in The mongol plot, Mariana, and Mariana and Novia que te vea - Paniagua Olivares, Ulises; García Ayala, José Antonio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This article addresses the relationship between the novel, the cinema and the city to reinterpret the imaginaries about the modernization of Mexico City between 1940 and 1970, through a methodology designed based on intertextual analysis and the Deep Hermeneutics Method. For this reason, three Mexican films are studied: El complot mongol, Mariana, Mariana, and Novia que te vea, and the novels from which they were adapted. In addition, the purpose is to analyze the modernization of this city during this period, where a sociohistorical context was consolidated with a tight control of the State.